Livestock and sustainability in changing climate: Impacts and global best practices - Wilkes, Andreas (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Presented by Andreas Wilkes, Values for Development Ldt, on 28 June 2021 at the Asian Development Bank (ADB) Webinar on Sustainable Livestock.